Exploring ESL teacher beliefs and classroom practices of CLT: A case study - Rahman, Mohammad Mosiur; Singh, Manjet Kaur Mehar; Pandian, Ambigapathy (Eskisehir Osmangazi University, 2018)
This paper presents a case study that investigated and compared the stated beliefs and observed classroom practices relating to Communicative Language Teaching (CLT) of two ESL teachers. The findings of the study revealed that both the teachers hold similar complex beliefs that mostly contradict the philosophy of CLT. The practices were not in line with their stated belief or CLT principles either. The findings also indicate that teachers indeed possess a set of complex beliefs that are not always realized in their classroom practices for a variety of potential reasons: some of these might be directly related to the context of teaching. Additionally, this study found that by articulating and reflecting on his beliefs, the teacher became more aware of the meaning and impact of these beliefs on his classroom practices. Some implications of future studies have also discussed.